E-COURT SEBAGAI REALISASI ASAS PERADILAN CEPAT, SEDERHANA DAN BIAYA MURAH DALAM PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - Sitohang, Mawar; Sinaga, Haposan Sahala Raja; Wijayati, Rr Ani; Siregar, Rospita Adelina; Widyani, I Dewa Ayu (Fakultas Hukum Universitas Kristen Indonesia, 2025)
The Industrial Relations Procedure Law by Law Number 2 of 2004 concerning Industrial Relations Dispute Resolution, regulates the procedures for resolving disputes through deliberation, mediation, conciliation, arbitration, and industrial relations courts, by applying the principles of fast, simple, and low-cost justice. The research method used is a normative juridical research method. The results of the study concluded that the time period for resolving industrial relations disputes is often not by the provisions stipulated in Law Number 2 of 2004, so it is necessary to get the attention of relevant parties in the dispute resolution process by using information technology platforms such as e-court in resolving industrial relations dispute cases as has begun to be applied to the settlement of disputes at the litigation level.